Bitter Melon—an Asian Vegetable Expanding in Florida - Guodong Liu; Qingren Wang; Yuncong Li; David Dinkins; Bonnie Wells; Yuqi Cui (EDIS, 2016)
Bitter melon is a tropical and subtropical vegetable crop with long climbing vines which is widely cultivated in Asia, Africa, and the Caribbean. The unripe fruit is used as a vegetable with a pleasantly bitter taste. This 7-page fact sheet provides an overview of this plant as well as recommendations for individuals in Florida who are interested in growing it. Written by Guodong Liu, Qingren Wang, Yuncong Li, David Dinkins, Bonnie Wells, and Yuqi Cui, and published by the UF Department of Horticultural Sciences, December 2015.